One‐year calorie restriction impacts gut microbial composition but not its metabolic performance in obese adolescents. (6th April 2017) - Ruiz, Alicia; Cerdó, Tomás; Jáuregui, Ruy; Pieper, Dietmar H.; Marcos, Ascensión; Clemente, Alfonso; García, Federico; Margolles, Abelardo; Ferrer, Manuel; Campoy, Cristina; Suárez, Antonio
Summary: Recent evidence has disclosed a connection between gut microbial glycosidase activity and adiposity in obese. Here, we measured microbial α‐glucosidase and β‐galactosidase activities and sorted fluorescently labeled β‐galactosidase containing (βGAL) microorganisms in faecal samples of eight lean and thirteen obese adolescents that followed a controlled calorie restriction program during one year. β‐galactosidase is a highly distributed functional trait, mainly expressed by members of Blautia, Bacteroides, Alcaligenes, Acinetobacter and Propionibacterium . Only long‐term calorie restriction induced clear changes in the microbiota of obese adolescents. Long‐term calorie restriction induced significant shifts in total and βGAL gut microbiota, reducing the Firmicutes : Bacteroidetes ratio and enhancing the growth of beneficial microorganisms such as Bacteroides, Roseburia, Faecalibacterium and Clostridium XIVa. Moreover, the structure and composition of βGAL community in obese after long‐term calorie restriction was highly similar to that of lean adolescents. However, despite this high compositional similarity, microbial metabolic performance was different, split in two metabolic states at a body mass index value of 25. Our study shows that calorie restriction is a strong environmental force reshaping gut microbiota though its metabolic performance is linked to host's adiposity, suggesting that functional redundancy and metabolic plasticity are fundamental properties of gut microbial ecosystem.